Employee compensation and benefits pre and post COVID-19 - Eriona Shtembari; Andromahi Kufo; Dea Haxhinasto (Administrative Sciences, 2022)
The Compensation and Benefits Package is considered the main employee's motivator. As such, it plays a crucial role in determining successful recruiting, engagement, and retention strategies. Failing to offer the right package, will be translated into additional costs. This study aimed to identify what type of compensation and benefits Albanian employees receive and their relationship with job satisfaction, before and after COVID-19. We surveyed 127 employees and conducted 10 in-depth interviews, in different institutions in Albania. Descriptive and inferential statistics were used to analyze the data. The findings showed that most received benefits are medical insurance and bonuses, and employees are less than considerably satisfied with their package. The majority stated that it had great importance in their job satisfaction, and most would leave their current job for another one that offers more benefits. Findings related to the COVID-19 impact showed that employees' lifestyle has changed and flexible working hours are the top benefit, followed by more paid time-off options. The conclusions of the study indicate that Compensations and Benefits packages should be redesigned to meet the needs of working in the "new normal", for current and future employees, paying close attention to their preferences.
Keywords: 350; COVID-19; compensation and benefit; HR; pandemic